PROFITABILITAS DAN DAMPAK MEDIASINYA TERHADAP NILAI PERUSAHAAN (Studi Empirik Pada Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2011-2015) - Akhmadi Akhmadi; Ariandini Ariadini (Sains: Jurnal Manajemen dan Bisnis, 2018)
The purpose of this study was to determine whether there is influence between firm growth and firm size to firm value, using profitability as an intervening variable. This type of research is descriptive and associative. The population of mining listed company on the Indonesia Stock Exchange period 2011-2015 by 41 companies using purposive sampling method obtained a sample of 28 companies. The data used is secondary data. Analysis of the data using the classical assumption test, partial test (t test) and path analysis. By using SPSS (Statistics Product and Service Solution) program 20 for windows. From the calculation, all the classical assumption has been fulfilled. The first regression equation namely, [ROA = 0.075 growth + 0.048 size + 0.996] and a second regression equation namely, [PBV = 0.101 growth + (-0.064) size + 0.454 roa + 0.880]. The results of research partially firm growth has no effect and not significant effect to firm value. Firm size has no effect and does not significant to firm value. Profitability positive and significant effect to firm value. The growth of the company has no effect and not significant on profitability. The size of the firm has no effect and is not significant on profitability. Path analysi of the test result showed that the profitability as intervening variable is unable to mediate the inffect of firm growth on firm value but its influence is not significant. Profitability as an intervening variable is able to mediate the effect of firm size on firm value but its effect is not significant.